Comparison of the Effect of Face-to-Face and Multimedia Education on the Anxiety Caused by Electroconvulsive Therapy in Patients with Mood Disorders - Saeed Vaghee; Mohsen Sepehrikia; Seyed Ali Saghebi; Hamidreza Behnam Voshani; Azam Salarhaji; Zohre Nakhaee Moghaddam (Mashhad University of Medical Sciences, 2017)
Background: Training methods to reduce the anxiety caused by the electroconvulsive therapy (ECT) should match the necessity of communicating with the patients suffering from mood disorders. Aim: This study aimed to compare the effects of face-to-face and multimedia education on the anxiety induced by the ECT. Method: This randomized controlled clinical trial was conducted on 75 patients with mood disorders undergoing ECT in the Ebn-e-Sina Psychiatric Hospital in Mashhad, Iran within 2013-2014 in three groups of face-to-face education (i.e., individual training), multimedia education (i.e., training through CD), and control (i.e., usual training), Receiving training for half an hour to get familiar with the ECT department, nursing care, and self-care one day before performing the ECT. The Spielberger's State-Trait Anxiety Inventory was completed prior to the intervention and before the first, middle, and final sessions of the ECT. The data were analyzed using the one-way and repeated measures ANOVA in the SPSS version 11.5. Results: According to the results of the study, 56% (n=14), 56% (n=14), and 48% (n=12) of the participants in the face-to-face, multimedia, and control groups were male, respectively. The post-hoc Tukey's test demonstrated that the control group had a significant difference with the face-to-face and (P=0.01) multimedia education groups (P=0.03) before the first session of the ECT. In addition, there was a significant difference between the face-to-face and multimedia education groups in this regard (P=0.07). Implications for Practice: Considering the conditions and facilities of the psychiatric hospitals, it is possible to use different methods of face-to-face or multimedia education to reduce the anxiety caused by the ECT.